Council of International Neonatal Nurses (COINN) Global Neonatal Provider Database Initiative (CGNPD): Results From an Implementation Focus Group. (December 2015) - Eklund, Wakako; Kenner, Carole
Abstract : Background: The neonatal nurses are the key component of the essential workforce necessary to address the healthcare needs of the infants globally. The paucity of the data regarding the availability and training of the neonatal workforce challenges the stakeholders at the regional, national, and global levels. The lack of these data makes strategic planning for initiatives especially in low-resourced countries difficult. Up-to-date data are critically needed to describe the role neonatal nurses play in global newborn health outcomes. Purpose: The purpose of the COINN Global Neonatal Provider Database Initiative (CGNPD) was to develop a workforce database by developing survey questions, conducting a focus group to determine the key reasons such a database was needed and how best to implement it, and incorporating these comments into the workforce survey and launch. Pilot testing of the draft survey instrument was done. This article reports on the findings from the focus group and the development of the survey. Methods: A qualitative design using the focus group method was used. The focus group discussions were guided by semi-structured interview questions that had been developed prior to the focus group by neonatal experts. A convenience sample of 14 members from the international delegates and project advisory members who attended the COINN 2013 in Belfast, Northern Ireland, participated. These participants represented 10 countries. Thematic analysis was conducted using verbatim transcripts of the focus group data. Results: Four main themes emerged: (1) the invisibility of neonatal nurses, (2) benchmarking needs for quality and standards, (3) need for partnership to implement the database, and (4) setting priorities for variables needed for the most salient database. Implications for Practice: The questionnaire examined participants' perceptions of the significance of and the future utilization of the workforce database and elements that should be included in the survey. Implications for Research: The global neonatal workforce database is needed to describe who the neonatal nurses are in each country, what they do, how they are trained, and where they work. The data from the focus group aided in the development of the workforce survey that has been pilot tested and provides critical information to guide COINN's global implementation of the database project.